Advances in catalytic dehydrogenation of ethanol to acetaldehyde. Issue 20 (5th October 2021) - Pang, Jifeng; Yin, Ming; Wu, Pengfei; Li, Xianquan; Li, Haoyu; Zheng, Mingyuan; Zhang, Tao
Abstract : This review summarizes the recent catalyst achievements in oxidative and non-oxidative dehydrogenation of ethanol, and analyzes the reaction mechanism over typical catalysts. Abstract : The rapid growth of ethanol production and its limited blending ratio in gasoline stimulates the conversion of ethanol into value-added chemicals and fuels. Dehydrogenation of ethanol to acetaldehyde provides an elegant option for ethanol conversion in view of versatile applications of acetaldehyde and the high atomic economy of this process. In this review, the recent progress in the catalytic conversion of ethanol to acetaldehyde is summarized and discussed. In particular, the representative catalysts for the oxidative and non-oxidative dehydrogenation of ethanol were highlighted, and reaction mechanisms over typical catalysts were analyzed. Finally, challenges in improving acetaldehyde selectivity and catalyst stability, and opportunities in replacing the fossil route acetaldehyde production were proposed.